Regeneration of Tracheal Tissue in Partial Defects Using Porcine Small Intestinal Submucosa - Nelson Bergonse Neto; Lianna Ferrari Jorge; Julio C. Francisco; Bruna Olandoski Erbano; Barbara Evelin Gonçalves Barboza; Larissa Luvison Gomes da Silva; Marcia Olandoski; Katherine Athayde Teixeira de Carvalho; Luiz Felipe Pinho Moreira; Jose Rocha Faria Neto; Eltyeb Abdelwahid; Luiz Cesar Guarita-Souza (Hindawi Limited, 2018)
Background. Surgical correction of tracheal defects is a complex procedure when the gold standard treatment with primary end-to-end anastomosis is not possible. An alternative treatment may be the use of porcine small intestinal submucosa (SIS). It has been used as graft material for bioengineering applications and to promote tissue regeneration. The aim of this study was to evaluate whether SIS grafts improved tracheal tissue regeneration in a rabbit model of experimental tracheostomy. Methods. Sixteen rabbits were randomized into two groups. Animals in the control group underwent only surgical tracheostomy, while animals in the SIS group underwent surgical tracheostomy with an SIS graft covering the defect. We examined tissues at the site of tracheostomy 60 days after surgery using histological analysis with hematoxylin and eosin (H&E) staining and analyzed the perimeter and area of the defect with Image-Pro® PLUS 4.5 (Media Cybernetics). Results. The average perimeter and area of the defects were smaller by 15.3% (p=0.034) and 21.8% (p=0.151), respectively, in the SIS group than in the control group. Histological analysis revealed immature cartilage, pseudostratified ciliated epithelium, and connective tissue in 54.5% (p=0.018) of the SIS group, while no cartilaginous regeneration was observed in the control group. Conclusions. Although tracheal SIS engraftment could not prevent stenosis in a rabbit model of tracheal injury, it produced some remarkable changes, efficiently facilitating neovascularization, reepithelialization, and neoformation of immature cartilage.